2014
DOI: 10.1152/ajpregu.00475.2013
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue thermogenesis contributes to emotional hyperthermia in a resident rat suddenly confronted with an intruder rat

Abstract: There is controversy concerning the contribution of nonshivering thermogenesis in brown adipose tissue (BAT) to emotional hyperthermia. In the present study we compared BAT, core body, and brain temperature, and tail blood flow, simultaneously measured, to determine whether BAT thermogenesis contributes to emotional hyperthermia in a resident Sprague-Dawley rat when an intruder rat, either freely-moving or confined to a small cage, is suddenly introduced into the cage of the resident rat for 30 min. Introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 62 publications
5
51
0
Order By: Relevance
“…In previous work for both BRAC and intruder models (35,45), we demonstrated that a ␤ 3 -adrenoceptor antagonist reduces the increases in both BAT and body temperatures. Similar findings have been reported in a social defeat model (29).…”
Section: Comparison Of Bat and Body Temperatures Provides An Index Ofmentioning
confidence: 60%
See 3 more Smart Citations
“…In previous work for both BRAC and intruder models (35,45), we demonstrated that a ␤ 3 -adrenoceptor antagonist reduces the increases in both BAT and body temperatures. Similar findings have been reported in a social defeat model (29).…”
Section: Comparison Of Bat and Body Temperatures Provides An Index Ofmentioning
confidence: 60%
“…In one group of animals, the intruder rat was able to move freely inside the resident rat's cage. In another group, the intruder rat was confined to a smaller cage, preventing physical contact with the resident rat (35).…”
Section: Experimental Protocolsmentioning
confidence: 99%
See 2 more Smart Citations
“…The animals remained in this condition for 15 min. This social novelty model has been adapted from two other models of social stress using intruder rats (Keeney et al, 2006;Mohammed et al, 2014).…”
Section: Experimental Designmentioning
confidence: 99%